Back to Tanganyika: a case of recent trans-species-flock dispersal in East African haplochromine cichlid fishes. Issue 3 (March 2015) - Meyer, Britta S.; Indermaur, Adrian; Ehrensperger, Xenia; Egger, Bernd; Banyankimbona, Gaspard; Snoeks, Jos; Salzburger, Walter
Abstract : The species flocks of cichlid fishes in the East African Great Lakes are the largest vertebrate adaptive radiations in the world and illustrious textbook examples of convergent evolution between independent species assemblages. Although recent studies suggest some degrees of genetic exchange between riverine taxa and the lake faunas, not a single cichlid species is known from Lakes Tanganyika, Malawi and Victoria that is derived from the radiation associated with another of these lakes. Here, we report the discovery of a haplochromine cichlid species in Lake Tanganyika, which belongs genetically to the species flock of haplochromines of the Lake Victoria region. The new species colonized Lake Tanganyika only recently, suggesting that faunal exchange across watersheds and, hence, between isolated ichthyofaunas, is more common than previously thought.